2011
DOI: 10.2119/molmed.2011.00069
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of Histone Deacetylases in Inflammatory Bowel Diseases

Abstract: This review, comprised of our own data and that of others, provides a summary overview of histone deacetylase (HDAC) inhibition on intestinal inflammation as well as inflammation-mediated carcinogenesis. Experimental colitis in mice represents an excellent in vivo model to define the specific cell populations and target tissues modulated by inhibitors of HDAC. Oral administration of either suberyolanilide hydroxamic acid (SAHA) or ITF2357 results in an amelioration in these models, as indicated by a significan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
63
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 67 publications
(63 citation statements)
references
References 81 publications
0
63
0
Order By: Relevance
“…47,51 This sensitizing activity may account for the reported ability of SAHA/Vorinostat to selectively enhance apoptosis in AOM-induced colon tumors and suppress their formation and growth. 47,[52][53][54] It is not clear, however, whether HDAC inhibitors are ideal for this purpose since they also cause changes in histone acetylation and gene expression systemically.…”
Section: Discussionmentioning
confidence: 99%
“…47,51 This sensitizing activity may account for the reported ability of SAHA/Vorinostat to selectively enhance apoptosis in AOM-induced colon tumors and suppress their formation and growth. 47,[52][53][54] It is not clear, however, whether HDAC inhibitors are ideal for this purpose since they also cause changes in histone acetylation and gene expression systemically.…”
Section: Discussionmentioning
confidence: 99%
“…From a therapeutic perspective, the immunomodulatory effects of VPA and other HDAC inhibitors might prove useful in different clinical settings where regulation of immunity is eagerly needed as in chronic inflammatory diseases (Glauben and Siegmund 2011) or in graft vs. host disease (GVHD) after allogeneic stem cell transplantation (Choi and Reddy 2011). Pioneering work from Reddy et al (2008) demonstrated that injection of DCs treated ex vivo with HDAC inhibitors reduced experimental GVHD in a murine allogeneic bone-marrow transplantation model, likely in relation with increased expression of indoleamine 2,3-dioxygenase (IDO), a suppressor of DC function, after exposure to HDAC inhibitors, in a signal transducer and activator of transcription-3 (STAT-3) dependent manner (Sun et al 2009).…”
Section: Discussionmentioning
confidence: 99%
“…However, given that HDAC inhibitors act against several or all 11 HDAC family members, clinical phase I trials have documented many side effects, such as diarrhea, electrolyte changes, weight loss, disordered clotting, fatigue, and cardiac arrhythmias (6). Similarly, recent studies have reported the use of HDAC inhibitors for amelioration of intestinal inflammation (22). However, the use of these drugs may be limited by other reports describing their effect as immunosuppressive drugs that block innate immunity and increase susceptibility to severe infections in vivo (4).…”
Section: Discussionmentioning
confidence: 99%